Reader's collection, Library of Congress Copyright Office drama deposits - Library of Congress. Copyright Office
Typewritten or handwritten play scripts deposited with the U.S. Copyright Office as unpublished and subsequently transferred to the Manuscript Division. Reflects the interests of early researchers and the desire of later curators to preserve rare samples of early drama. Genres include farce, melodrama, musicals, satire, and vaudeville. Subjects include city life, ethnic and immigrant groups, exploration, foreign influences, inventions, plight of the poor, theater, and style of the wealthy.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Forms part of: Library of Congress Copyright Office drama deposits collection.
Selected play scripts were transferred from Library of Congress Copyright Office drama deposits (LCCN mm 85061908).
Keywords: American drama -- Foreign influences; City and town life; Drama -- Stories, plots, etc; Ethnic groups; Farce; Immigrants; Inventions; Melodrama; Musicals; Poor; Rich people; Satire; Vaudeville; America -- Discovery and exploration